The Relationship of Global Exposure and Intercultural Effectiveness among Secondary Youth - Stacy K. Vincent; Courtney Turley; Ashley L. Austin (Journal of International Agricultural and Extension Education, 2020)
This study evaluated the impact of varying amounts of global exposure and previous travel experiences have on secondary agriculture students’ intercultural effectiveness (ICE) and global experiences through the lens of Mere Exposure Theory. Using a descriptive correlational approach, we surveyed 387 secondary agriculture seniors from 11 randomly selected schools in Kentucky to evaluate participant self-awareness, exploration, global mindset, relationship interest, positive regard, and emotional resilience. Findings revealed the majority of participants excelled in exploration but lacked in global mindsets. Benefits of successful ICE when applied are expected to increase communication and work effectiveness. Ignoring this approach would create poor abilities to connect with individuals of different cultural backgrounds.
Keywords: intercultural effectiveness; global exposure; youth; agricultural education; mere exposure